Climate Smart Villages: A Community Approach to Climate Resilient Agriculture and Sustainable Livelihoods - Kimeli, Philip; Nyasimi, Mary; Mungai, Catherine; Kinyangi, James; Radeny, Maren A.O.; Recha, John W.M. (African Centre for Technology Studies, 2017)
The majority of Africa’s people derive livelihoods from the agricultural sector. However, a rapidly changing climate hinders the continent from realizing its full potential in agriculture. Emerging patterns of climate variability and climate change have raised the level of vulnerability for rural communities, as their current agricultural practices and institutional coping mechanisms cannot handle the changes. Therefore, adapting agriculture to methods of dealing with climate change ought to be considered as central to building climate resilient livelihoods and economic systems in Africa. In the search for answers, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has been working with a vast range of research and development partners to test a portfolio of climate smart agriculture (CSA) interventions in selected villages (Climate Smart Villages (CSVs) in Nyando, Kenya. There are over 2,000 households in the CSVs involved in participatory action research processes and field-based learning approaches that provide opportunities for adaptive learning and innovation that builds household and community resilience. This chapter sets out to: a) discuss the CSVs model as a community-based approach that builds resilience, achieves food security and enhances sustainable livelihoods; b) describe the portfolio of CSA practices — ideally ones that have been assessed for local climatic and environmental suitability, gender and social equity — that farmers are using; and c) discuss processes of scaling up the CSVs approach through policy processes to reach more farmers across eastern Africa.